IDENTIFICATION OF EPIDEMIOLOGICAL RISK FACTORS FOR HEPATITIS C IN PUNJAB, PAKISTAN - Ghias, Muhammad; Pervaiz, Muhammad Khalid (Journal of Ayub Medical College Abbottabad, 2009)
Background & Objectives: Hepatitis C virus (HCV) is one of the major health issues in Punjab, Pakistan. About 3% of the world population have been infected by hepatitis C virus. The objective of this study was to find out significantly associated factors with Hepatitis C in the region. Demographic, socio-economic and clinical factors were taken in consideration to determine the predictive strength of these associated factors by the logistic regression model approach. Methods: This was a hospital based case-control study of 400 patients; out of which 119 were controlled patients (HCV negative) while 281 were cases (HCV positive). Patients admitted in gastroenterology wards of Jinnah, Shaikh Zayed, and Mayo hospitals in Lahore city were interviewed to gather risk factors information. Data was collected in six months starting from April 2006 to September 2006. Results: results from multiple linear logistic regression model for overall data showed that age (OR=1.035, p=0.001), history of blood transfusion (OR=9.204, p=0.004), history of hospitalization (OR=2.979, p=0.043), Tattooing (OR=27.484, p=0.013), family history of hepatitis (OR=4.069, p=0.000), surgical operation (OR=4.290, p=0.030) were found to have significant and positively association with Hepatitis C. Conclusion: Hence our estimated logit model can be used to predict the chance of hepatitis C under the presence or absence of certain significant factors. Keywords: Hepatitis C, Risk factors, Logistic regression, Odds Ratio, Pakistan